학령전기 단순언어장애 및 일반아동의 문법성 메타언어인식과 집행기능 수행능력 비교분석 - 임동선(Dong Sun Yim); 양윤희(Yoon Hee Yang); 조연주(Yeon Joo Jo); 이지연(Ji Yeon Lee); 성지민(Ji Min Seong) (언어치료연구, 2015)
목적: 본 연구에서는 작업기억, 억제조절, 전환 능력을 포괄하는 상위인지능력인 집행기능 과제와 메타언어인식 능력을 측정할 수 있는 문법성 판단 과제 수행을 비교 분석하고 집행기능 하위요소 중 학령전기 단순언어장애 및 일반아동 각 집단의 문법성 메타언어인식 능력을 가장 잘 설명해줄 수 있는 능력은 다른지 확인하고자 하였다. 방법: 만 5-6세의 아동 40명(단순언어장애아동 16, 일반아동24)을 대상으로 언어성 작업기억(CLPT), 비언어성 작업기억(Matrix backward), 억제조절(SST: Stop Signal Task), 전환(DCCS: Dimensional Change Card Sort) 그리고 문법성 판단(GJT: Grammatical Judgment Task) 과제를 실시하였다. 통계적 처리는 분산분석, 상관분석 및 단계적 회귀분석을 실시하였다. 결과: 단순언어장애 아동은 또래 일반 아동에 비해 언어성 작업기억(CLPT), 억제조절(SST), 전환(DCCS) 과제 그리고 문법성 판단(GJT)에서 유의하게 낮은 정확도를 보였으며, 비언어성 작업기억(Matrix b), 과제에서는 또래 아동과 비슷한 수행을 보였다. 한편, 일반아동 집단에서는 언어성 작업기억력(CLPT)이 문법성판단-정문(G) 조건을 예측해주었고, 억제조절-GO(SST_GO) 조건이 문법성 판단-비문(U) 조건을 유의하게 예측해주었으며, 단순언어장애 집단에서는 유의한 설명요인이 나타나지 않았다. 결론: 단순언어장애 아동에게 상대적으로 비언어성 작업기억 능력은 잔존해있으며, 일반 아동 집단에서는 언어성 작업기억 및 억제조절과 같은 집행기능이 문법성 메타언어인식 능력을 설명해주지만, 단순언어장애 아동 집단에서는 집행기능과 문법성 메타언어인식 능력 간의 관계가 견고하지 않았다. 이는 임상 현장에서 단순언어장애 아동의 언어능력을 증진시키기 위하여 작업기억, 억제조절, 전환 등 다양한 집행기능 요소들을 개별적으로 접근하기 보다는 한 회기 내에서도 긴밀하게 연결될 수 있도록 통합적으로 계획하는 것이 필요할 수 있음을 시사한다. Purpose: The purpose of the study is to identify whether children with and without SLI show differences in performance on each subtype of executive functioning and grammatical judgment task, whether these factors correlate with each other, and whether these subtypes of executive functioning predict children's meta-linguistic awareness skills measured by a grammaticality judgment task. Methods: Forty children (SLI 16, NL 24) between the ages of 5 and 6 participated in this study. The experimental tasks were working memory (CLPT: Competing Language Processing Task/ Matrix backward), SST (Stop Signal Task), DCCS (Dimensional Change Card Sort), and GJT (Grammatical Judgment Task). For data analysis, repeated measure of ANOVA, Pearson's correlation, and stepwise multiple regression were used. Results: There were significant differences on all tasks except non-linguistic working memory (Matrix backward) between the two groups. The strongest predictor of GJT (Grammatical condition) was linguistic WM (CLPT), and it was the SST (GO) task which significantly predicted GJT (Un-grammatical condition) in the NL group. However, in the SLI group, there was no variable which correlated with GJT. Conclusions: The results indicated that non-linguistic WM capacity was comparable between groups, and linguistic WM (CLPT), SST (GO) were important factors in the preschool-age NL group in which this trend was not found in the SLI group. It is necessary to plan to completely link each executive function such as working memory, inhibitory control, and shifting in clinical sessions to improve the language skills of children with language impairment. KCI Citation Count: 9